(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
The article describes the structure and technical characteristics of the device for loading dry fertilizers, dry mixed fodder and similar crushed masses into bags and performing similar functions, as well as the principle of its operation. This device is very different from other devices due to its compactness and mobility. It is recommended to use this type of device for businesses and small private enterprises.